2006
DOI: 10.1002/mds.20758
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of artistic productivity in Parkinson's disease

Abstract: References1. Burn DJ, Troster AI. Neuropsychiatric complications of medical and surgical therapies for Parkinson's disease.Enhancement of pre-existing artistic talent as well as the emergence of a new artistic tendency has been associated with frontotemporal dementia (FTD) 1,2 but is an unusual finding in Parkinson's disease (PD). 3 Conversely, available case studies and anecdotal reports have shown that PD does not adversely affect the artistic expression of established artists. 4 We present a patient who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 5 publications
1
39
0
Order By: Relevance
“…The specific artistic style he adopted emphasized larger amplitude proximal movements that were relatively preserved. Chatteijee et al (Chatterjee et ai., 2006) suggested that a possible mechanism that might influence this discrepancy between spontaneous movements and those involved in painting might be related to differences in proximal versus distal target reaching, an observation previously described in PD (Chatterjee et Bindler et al, 2011Canesi et al, 2012Chatterjee et al, 2006Kulisevsky et al, 2009Pinker, 2002Schräg & Trimble, 2001Schwingenschuh et al, 2010Walker et al, 2006Witt et al, 2006 Age Note. LD = levodopa; DA = dopamine agonist; CBG = cabergoline; LIS = lisuride; PRG = pergolide; PRX = pramipexole; ROP = ropinirole-ROT = Rotigotine; NA = not available.…”
Section: The Form Of Artmentioning
confidence: 89%
“…The specific artistic style he adopted emphasized larger amplitude proximal movements that were relatively preserved. Chatteijee et al (Chatterjee et ai., 2006) suggested that a possible mechanism that might influence this discrepancy between spontaneous movements and those involved in painting might be related to differences in proximal versus distal target reaching, an observation previously described in PD (Chatterjee et Bindler et al, 2011Canesi et al, 2012Chatterjee et al, 2006Kulisevsky et al, 2009Pinker, 2002Schräg & Trimble, 2001Schwingenschuh et al, 2010Walker et al, 2006Witt et al, 2006 Age Note. LD = levodopa; DA = dopamine agonist; CBG = cabergoline; LIS = lisuride; PRG = pergolide; PRX = pramipexole; ROP = ropinirole-ROT = Rotigotine; NA = not available.…”
Section: The Form Of Artmentioning
confidence: 89%
“…Creative motivation, like motivation in general, increases in some patients taking dopaminergic agents. 29,87 Motivation may be strongest with chronic administration of the less sedating agonists, less sedating DA agonists seem preferable, and D3 receptor binding may be important. 88 Unfortunately, DA agonists can also cause impulse control problems, gambling addiction, compulsive spending, hypersexuality, and hallucinations.…”
Section: Dopaminergic Drugsmentioning
confidence: 99%
“…While changes in artistic productivity and style have been related to cortical degeneration in FTD, AD, and CBD, the present case report suggests that changes in creativity and artistic output in PD may be more related to dopaminergic imbalance in the limbic system. Impulse control disorders (ICDs) have been observed previously in PD patients reported to have shown changes in their creative expression [6][7][8]. In one report, a 'strong urgency' and great interest in painting suggestive of the development of punding was also described [8].…”
Section: Discussionmentioning
confidence: 89%
“…In Alzheimer's disease (AD) [4] and corticobasal degeneration (CBD) [5], increasing abstraction with no deliberate stylistic effort has been associated with global cognitive impairment and visuospatial deficits. In Parkinson's disease (PD), emergence of poetic talent [6] and compulsive augmentation of artistic productivity [7,8] have been reported in association with dopaminergic druginduced hypomania [6], behavioural disinhibition and obsessive-compulsive behaviour [7,8].…”
Section: Introductionmentioning
confidence: 99%